Secondary battery
The secondary battery design addresses the issue of deteriorated battery characteristics by incorporating particles with a metal portion and an oxide layer in the positive electrode active material, enhancing lithium ion mobility and preventing internal short-circuits, thus maintaining better cycle maintenance rates and longer storage times.
Patent Information
- Application Number
- JP2023166475
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-09
Smart Images

Figure 2025056934000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a secondary battery. [Background technology]
[0002] Patent Documents 1 to 3 describe lithium ion secondary batteries using a lithium metal composite oxide as a positive electrode active material. Known lithium ion secondary batteries include a configuration in which the positive electrode active material is coated with an oxide (e.g., Patent Document 1) and a configuration in which an oxide layer is provided between the positive electrode active material and the separator (e.g., Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2013-131437 A [Patent Document 2] JP 2016-225277 A [Patent Document 3] JP 2009-135084 A Summary of the Invention [Problem to be solved by the invention]
[0004] In such a secondary battery, if an oxide is provided in the positive electrode active material, the movement of lithium ions is restricted, and there is a possibility that the battery characteristics will deteriorate.
[0005] An object of the present invention is to provide a secondary battery capable of suppressing deterioration of battery characteristics. [Means for solving the problem]
[0006] A secondary battery according to one embodiment has a positive electrode, a negative electrode, and a non-aqueous electrolyte solution, the positive electrode including a positive electrode active material and a plurality of particles including an oxide and a metal portion, and the oxide included in each of the plurality of particles includes at least one of copper oxide, iron oxide, nickel oxide, and zinc oxide. Effect of the Invention
[0007] According to the secondary battery of the present invention, the deterioration of the battery characteristics can be suppressed. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic configuration of a secondary battery according to an embodiment. [Diagram 2] FIG. 2 is an explanatory diagram that illustrates a schematic configuration of particles contained in the positive electrode. [Diagram 3] FIG. 3 is a table showing the configurations and battery characteristics of secondary batteries (coin cells) according to examples and comparative examples. [Figure 4] FIG. 4 is a graph showing the results of measuring the LSV of the secondary battery (coin cell) according to the example. [Diagram 5] FIG. 5 is a graph showing the results of measuring the LSV of a secondary battery (coin cell) according to a comparative example. [Figure 6] FIG. 6 is a photograph showing the results of SEM-EDX observation of particles according to the example. [Figure 7] FIG. 7 is a table showing the analysis results of the positive electrode active material according to the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described. Note that the present disclosure is not limited to these embodiments.
[0010] (Embodiment) Fig. 1 is a cross-sectional view showing the configuration of a secondary battery according to an embodiment. Fig. 2 is an explanatory diagram showing a schematic configuration of particles in a positive electrode. As shown in Fig. 1, a secondary battery 1 according to an embodiment has an electrode laminate 100 in which a positive electrode 21, a negative electrode 22, and a separator 23 are laminated. The positive electrode 21 and the negative electrode 22 are laminated with the separator 23 interposed therebetween. The secondary battery 1 according to an embodiment is a lithium ion secondary battery in which the capacity of the negative electrode 22 is obtained by occlusion and release of lithium (Li).
[0011] The positive electrode 21 has a positive electrode current collector 21A and a positive electrode active material layer 21B provided on one surface of the positive electrode current collector 21A. The negative electrode 22 has a negative electrode current collector 22A and a negative electrode active material layer 22B provided on one surface of the negative electrode current collector 22A.
[0012] The separator 23 separates the positive electrode 21 and the negative electrode 22, and allows lithium ions to pass through while preventing a short circuit of current caused by contact between the two electrodes. In the example shown in Fig. 1, the separator 23 is provided between the positive electrode active material layer 21B of the positive electrode 21 and the negative electrode active material layer 22B of the negative electrode 22. The separator 23 has a first surface S1 in contact with the positive electrode active material layer 21B of the positive electrode 21 and a second surface S2 in contact with the negative electrode active material layer 22B of the negative electrode 22 on the side opposite to the first surface S1, and is formed on the surface of the positive electrode 21 or the negative electrode 22.
[0013] 1, the positive electrode active material layer 21B of the positive electrode 21 is provided on one side of the positive electrode current collector 21A, but may be provided on both sides of the positive electrode current collector 21A. Similarly, the negative electrode active material layer 22B of the negative electrode 22 is provided on one side of the negative electrode current collector 22A, but may be provided on both sides of the negative electrode current collector 22A. In addition, the electrode laminate 100 has three layers of the positive electrode 21, the separator 23, and the negative electrode 22 laminated, but is not limited thereto and may have four or more layers laminated.
[0014] The positive electrode current collector 21A of the positive electrode 21 is formed of a conductive material such as aluminum (Al). The positive electrode current collector 21A is not limited to aluminum, and may be other conductive materials such as nickel or stainless steel.
[0015] The positive electrode active material layer 21B of the positive electrode 21 includes a positive electrode active material and a plurality of particles 30 (see FIG. 2). The positive electrode active material layer 21B may also include a conductive agent and a binder, if necessary. The positive electrode active material is a positive electrode material capable of absorbing and releasing lithium ions, and for example, a lithium-containing composite oxide is used. For example, lithium cobalt oxide, lithium nickel oxide, lithium manganate, lithium iron phosphate, etc. may be used as the lithium-containing composite oxide. Alternatively, a part of the transition metal contained in these materials may be replaced with another metal.
[0016] As shown in FIG. 2, the particle 30 included in the positive electrode active material layer 21B of the positive electrode 21 has a metal part 31 and an oxide 32. The metal part 31 is surrounded by the oxide 32 and exists inside the particle 30. The oxide 32 exists on the surface layer of the particle 30 and covers the metal part 31. Although not shown, the plurality of particles 30 (metal part 31 and oxide 32) exist from one surface of the positive electrode active material layer 21B to the other surface of the positive electrode active material layer 21B in the thickness direction of the positive electrode 21. More preferably, the plurality of particles 30 exist substantially uniformly in the thickness direction of the positive electrode active material layer 21B. That is, in a cross-sectional view, the number of particles 30 per predetermined area is formed substantially equally across the region on one surface side of the positive electrode active material layer 21B, the central part of the positive electrode active material layer 21B, and the region on the other surface side of the positive electrode active material layer 21B.
[0017] The metal portion 31 includes at least one of metal materials such as copper (Cu), iron (Fe), nickel (Ni), zinc (Zn), etc. The oxide 32 includes at least one of copper oxide, iron oxide, nickel oxide, and zinc oxide.
[0018] The thickness t1 of the metal part 31 is, for example, 11 μm or less. The thickness t2 of the oxide 32 is, for example, 2 μm or more and 8 μm or less. In FIG. 2, the particles 30 are shown in a circular shape for ease of understanding. However, the shape of the particles 30 is not limited to this, and the particles 30 may be other shapes such as an elliptical shape or an irregular shape.
[0019] Returning to FIG. 1, the conductive agent contained in the positive electrode active material layer 21B is, for example, a carbon material such as carbon black. The conductive agent is not limited to one type, and a mixture of multiple conductive materials may be used. Note that the conductive agent may be a metal material, a conductive polymer, or the like, as long as it is a material having conductivity.
[0020] The binder contained in the positive electrode active material layer 21B is, for example, polyvinylidene fluoride (PVDF). However, the binder is not limited thereto, and may be any compound containing one or more of synthetic rubbers and polymeric compounds. Synthetic rubbers include styrene butadiene rubbers, fluorine-based rubbers, and ethylene propylene diene. Polymeric compounds include polyvinylidene fluoride, polyimide, and carboxymethyl cellulose.
[0021] The negative electrode current collector 22A of the negative electrode 22 is formed of a conductive material such as copper (Cu). The negative electrode current collector 22A is not limited to copper, and may be made of other conductive materials such as nickel or stainless steel.
[0022] The negative electrode active material layer 22B of the negative electrode 22 contains a negative electrode active material and a binder. The negative electrode active material is, for example, a carbon material such as graphite, a silicon compound (SiO x ) and the like. More specifically, the carbon material used in the negative electrode active material is, for example, at least one of graphitizable carbon, non-graphitizable carbon, and graphite (natural graphite and artificial graphite). The carbon material used in the negative electrode active material undergoes very little change in crystal structure when absorbing and releasing lithium ions, and therefore can provide high energy density and excellent cycle characteristics.
[0023] The binder contained in the negative electrode active material layer 22B is made of the same material as the binder contained in the above-mentioned positive electrode active material layer 21B, for example, polyvinylidene fluoride (PVDF). However, the binder contained in the negative electrode active material layer 22B may be made of the same material as the binder contained in the positive electrode active material layer 21B, or may be made of a different material.
[0024] The separator 23 separates the positive electrode 21 and the negative electrode 22, and allows lithium ions to pass through while preventing a short circuit of current caused by contact between the two electrodes. The separator 23 is formed of a thin film containing a polymer compound such as polyethylene. However, the separator 23 is not limited to this, and may be composed of a porous film formed of other resin materials.
[0025] The electrode laminate 100 is housed in a case (exterior body) not shown and sealed in the case. The electrolyte is impregnated into the positive electrode 21, the negative electrode 22, and the separator 23. The electrolyte includes an electrolyte salt and a solvent that dissolves the electrolyte salt. The electrolyte salt includes a lithium salt such as lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium bis(pentafluoroethanesulfonyl)imide (LiN(SO2C2F5)2), or lithium hexafluoroarsenate (LiAsF6).
[0026] The solvent is a non-aqueous solvent including, for example, a lactone-based solvent such as γ-butyrolactone, γ-valerolactone, δ-valerolactone, or ε-caprolactone; a carbonate-based solvent such as ethylene carbonate, propylene carbonate, butylene carbonate, vinylene carbonate, dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate; an ether-based solvent such as 1,2-dimethoxyethane, 1-ethoxy-2-methoxyethane, 1,2-diethoxyethane, tetrahydrofuran, or 2-methyltetrahydrofuran; a nitrile-based solvent such as acetonitrile; a sulfolane-based solvent; phosphoric acids; phosphate ester solvents; or pyrrolidones.
[0027] As described above, in this embodiment, the particles 30 including the metal portion 31 and the oxide 32 are substantially uniformly present inside the positive electrode active material layer 21B. Therefore, compared to a case where the oxide is formed in a layer covering the positive electrode active material layer 21B, it is possible to suppress the oxide from impeding the movement of Li ions. Furthermore, in this embodiment, since the metal portion 31 is surrounded by the oxide 32, the elution of metal ions from the metal portion 31 is suppressed. This makes it possible to suppress the occurrence of an internal short circuit in the secondary battery 1. Furthermore, the particles 30 may be bonded to the active material particles.
[0028] (Example) FIG. 3 is a table showing the configuration and battery characteristics of secondary batteries (coin cells) according to the Examples and Comparative Examples. FIG. 4 is a graph showing the results of measuring the LSV of the secondary battery (coin cell) according to the Examples. FIG. 5 is a graph showing the results of measuring the LSV of the secondary battery (coin cell) according to the Comparative Example. FIG. 6 is a photograph showing the results of SEM-EDX observation of particles according to the Examples. FIG. 7 is a table showing the results of analysis of the positive electrode active material according to the Examples. Note that the present invention is not limited to these Examples.
[0029] Example 1 The positive electrode active material according to Example 1 was prepared by the following method. Aluminum sulfate, cobalt sulfate, and nickel(II) sulfate heptahydrate were weighed out so that aluminum (Al) and cobalt (Co) were each 10% by weight relative to nickel (Ni). The aluminum sulfate, cobalt sulfate, and nickel(II) sulfate heptahydrate were dissolved in distilled water to a concentration of 1.5 mol / L to obtain an aqueous sulfate solution. Ammonium was also dissolved in distilled water to a concentration of 1.5 mol / L to obtain an aqueous ammonium solution.
[0030] Next, distilled water was placed in a 2L reaction vessel and heated to 50°C with a heater. The sulfate aqueous solution and ammonium aqueous solution were added while stirring the solution in the reaction vessel with a paddle-type stirring blade. The sulfate aqueous solution was added at a rate of 5.0 g / min. The ammonium and sodium hydroxide aqueous solutions were added so as to maintain the pH at 11.0. Each solution was added over a period of 24 hours, causing a coprecipitate to form.
[0031] The obtained coprecipitate was washed by repeatedly filtering under pressure and dispersing in distilled water to remove impurity ions. The washing was stopped when the electrical conductivity of the filtrate became less than 20 mS / m. The washed coprecipitate was heated at 100°C for 10 hours and dried.
[0032] Next, the obtained coprecipitate and lithium hydroxide were mixed so that the molar ratio of Li to the total amount of transition metal elements (X) (Li / X) was 1.04. This was pre-calcined at 500°C for 5 hours in an oxygen atmosphere, and then calcined at 730°C for 16 hours to obtain a positive electrode active material made of a composite oxide. The analysis results of the positive electrode active material are shown in Table 2 of FIG. 7. Note that FIG. 7 shows the analysis results for each different calcination temperature.
[0033] (Ni powder added) To the obtained positive electrode active material, Ni powder was added.
[0034] (Oxidation treatment) Ni powder was added to the positive electrode active material, stirred and mixed, and then oxidation treatment was performed. In the oxidation treatment, the temperature was increased at 5°C / min, the maximum temperature was reached at 300°C, and the temperature was kept at 30°C for 20 hours in an oxygen atmosphere. The material was then crushed in a mortar and coarse particles were removed using a filter with a mesh size of 90 μm. The surface layer of the Ni powder was oxidized by the oxidation treatment to form an oxide, and the unoxidized portion (unoxidized portion) inside the powder remained as a metal portion. This resulted in the formation of particles containing a metal portion and an oxide.
[0035] (Electrode preparation) The baked positive electrode active material, binder, conductive additive, and NMP (N-methylpyrrolidone) solvent were weighed out in a predetermined ratio and mixed to prepare a positive electrode slurry. A coating machine was used to prepare a positive electrode slurry with an electrode area density of 18 mg / cm. 2 The positive electrode slurry was applied so that the volume density of the electrode was 3.2 g / cm. 3 The press was carried out to make it look like this.
[0036] (Coin cell production) A metallic lithium (Li) disk (thickness 0.24 mm, diameter 17 mm) was prepared by punching. The punched metallic lithium (Li) disk was laminated on a stainless steel (SUS) plate (thickness 200 μm) as a negative electrode layer. This plate was placed in a stainless steel anode cup with the metallic lithium negative electrode layer facing up.
[0037] Thereafter, a polyolefin separator was punched out into a disk shape (thickness 15 μm, φ17.5 mm) by punching, and the separator was laminated on the lithium negative electrode material layer.
[0038] The separator was impregnated with 150 μL of the electrolyte, and the electrolyte was allowed to penetrate into the voids in the negative electrode.
[0039] Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were used as the electrolyte, and a mixed solvent was prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a mass ratio of EC:EMC = 3:7. Lithium hexafluorophosphate (LiPF6) was dissolved as a solute (electrolyte salt) in the mixed solvent at 1 mol / L to prepare a liquid electrolyte (non-aqueous electrolyte).
[0040] The positive electrode sheet was laminated on the separator with the positive electrode layer facing down, and then an aluminum plate was laminated on the aluminum foil (positive electrode current collector) of the positive electrode sheet.
[0041] Finally, a stainless steel cathode cup was laminated onto the aluminum plate.
[0042] A coin cell (2016 type) was produced by placing a gasket (insulating material) between the periphery of the anode cup and the periphery of the cathode cup and then sealing the anode cup and cathode cup with a crimping machine to form an outer casing.
[0043] (Metal and oxide thickness measurement) Figure 6(a) is a photograph showing the results of SEM observation of the particle cross section, Figure 6(b) is an oxygen mapping image showing the results of SEM-EDX observation of the particle cross section, and Figure 6(c) is a Ni mapping image showing the results of SEM-EDX observation of the particle cross section.
[0044] In measuring the thickness of the metal part and the oxide, as shown in FIG. 6(a), the cross section of the oxidized particle is imaged by SEM (Hitachi High-Tech, model S4800) or TEM (FE-TEM / EDX (JEOL JEM-F200 / Noran system 7)), and element mapping is performed by EDX as shown in FIG. 6(b) and FIG. 6(c). From the mapping of the element of the metal part (Ni in FIG. 6(c)) shown in FIG. 6(c) and the mapping of oxygen shown in FIG. 6(b), the thickness of each of the metal part and the oxide is measured by SEM. The part where oxygen is not detected is the metal part (unoxidized). The weight ratio of the metal part (unoxidized) contained in the oxide is calculated from the peak intensity ratio of the oxide and the metal part (unoxidized) in XRD.
[0045] (Battery evaluation) An initial charge / discharge test was performed on each coin cell produced in the examples and comparative examples using a commercially available charge / discharge characteristic evaluation device. In the initial charge / discharge test, each coin cell produced in the examples and comparative examples was charged at a constant current and constant voltage of 0.1 C to an upper limit voltage of 4.25 V and a lower limit current of 0.005 C in a thermostatic chamber at 25° C. After charging, the cells were rested for 10 minutes and then discharged at a current of 0.1 C to a lower limit voltage of 2.0 V.
[0046] The coin cells produced in the examples and comparative examples were all able to perform initial charging and discharging, and were found to function as secondary batteries.
[0047] 3, evaluation item A is the time (hr) until a short circuit occurs when fully charged and stored at 80° C. Evaluation item B is the dissolution current value (A) at 4.5 V in CV (Cyclic Voltammetry). Evaluation item C is the cycle retention rate.
[0048] (Cycle test) A charge-discharge cycle test was carried out in a thermostatic chamber at 60° C. according to the following steps (1) to (4).
[0049] (1) The coin cells produced in the examples and comparative examples were each subjected to constant current / constant voltage charging at a current of 1.0 C up to an upper limit voltage of 4.25 V / lower limit current of 0.01 C. Note that each coin cell produced in the examples and comparative examples was used after a 3-hour rest period.
[0050] (2) After charging, there was a one-minute rest period.
[0051] (3) Discharge was performed at a current of 5.0 C down to the lower limit voltage of 2.5 V.
[0052] (4) After discharging, a 5-minute rest period was allowed.
[0053] This charge-discharge test was performed for 100 cycles. After each charge-discharge cycle test, the discharge capacity of the coin cells manufactured in the examples and comparative examples was determined. The cycle retention rate was calculated as the ratio of the discharge capacity according to the following formula (1).
[0054] Cycle retention rate (%) = (discharge capacity after 100 cycles) / (discharge capacity after 1 cycle) × 100 (1)
[0055] (LSV measurement) Figures 4 and 5 show the results of LSV (Linear Sweep Voltammetry) measurements of the coin cells produced in the examples and comparative examples. In the LSV measurements, the electrode potential was swept over a specified range (3.0 V to 4.3 V in Figures 4 and 5), and the corresponding reaction current was measured.
[0056] Example 2 The oxidation treatment conditions of Example 2 are different from those of Example 1. Specifically, the oxidation treatment of Example 2 was performed in an oxygen atmosphere with a temperature rise time of 5°C / min, a maximum temperature of 500°C, and a holding time of 20 hours. The other manufacturing conditions of the coin cell and the battery evaluation were the same as those of Example 1.
[0057] Example 3 The oxidation treatment conditions of Example 3 are different from those of Example 1. Specifically, the oxidation treatment of Example 3 was performed in an oxygen atmosphere with a temperature rise time of 5°C / min, a maximum temperature of 700°C, and a holding time of 20 hours. The other coin cell production conditions and battery evaluation were the same as those of Example 1.
[0058] (Examples 4 to 6) Examples 4 to 6 are different from Examples 1 to 3 in that Cu powder is added to the positive electrode active material. The conditions of the oxidation treatment in Example 4 are the same as those in Example 1. The conditions of the oxidation treatment in Example 5 are the same as those in Example 2. The conditions of the oxidation treatment in Example 6 are the same as those in Example 3. The other coin cell production conditions and battery evaluations in Examples 4 to 6 are the same as those in Example 1.
[0059] (Examples 7 to 9) Examples 7 to 9 are different from Examples 1 to 3 in that Fe powder is added to the positive electrode active material. The conditions of the oxidation treatment in Example 7 are the same as those in Example 1. The conditions of the oxidation treatment in Example 8 are the same as those in Example 2. The conditions of the oxidation treatment in Example 9 are the same as those in Example 3. Other coin cell production conditions and battery evaluations in Examples 7 to 9 are the same as those in Example 1.
[0060] (Examples 10 to 12) Examples 10 to 12 are different from Examples 1 to 3 in that Zn powder is added to the positive electrode active material. The conditions of the oxidation treatment in Example 10 are the same as those in Example 1. The conditions of the oxidation treatment in Example 11 are the same as those in Example 2. The conditions of the oxidation treatment in Example 12 are the same as those in Example 3. Other coin cell production conditions and battery evaluations in Examples 10 to 12 are the same as those in Example 1.
[0061] (Comparative Example 1 to Comparative Example 4) The conditions under which the oxidation treatment was not performed are different in Comparative Examples 1 to 4 compared to the above-mentioned Examples 1, 4, 7, and 10. The other coin cell production conditions and battery evaluations in Comparative Examples 1 to 4 were the same as those in Examples 1, 4, 7, and 10.
[0062] (Comparative Examples 5 to 8) The oxidation treatment conditions of Comparative Example 5 to Comparative Example 8 are different from those of the above-mentioned Examples 1, 4, 7, and 10. Specifically, in the oxidation treatments of Comparative Example 1 to Comparative Example 4, the temperature rise time was 5° C. / min, the maximum temperature reached was 900° C., and the holding time was 20 hours, and the treatments were performed in an oxygen atmosphere. The other coin cell production conditions and battery evaluations of Comparative Example 1 to Comparative Example 4 were the same as those of Examples 1, 4, 7, and 10.
[0063] 3, in Examples 1 to 12, the weight ratio of the oxide increases as the maximum temperature reached in the oxidation treatment increases. Also, the thickness of the oxide increases as the maximum temperature reached in the oxidation treatment increases, and the thickness of the metal portion decreases.
[0064] As shown in Examples 1 to 12, the thickness of the oxide is 2 μm or more and 8 μm or less. More specifically, in Examples 1 to 3, the thickness of the oxide is about 2.2 μm or more and 7.1 μm or less, and the thickness of the metal part (unoxidized) is about 0.8 μm or more and 10.7 μm or less. In Examples 4 to 6, the thickness of the oxide is about 2.1 μm or more and 7.3 μm or less, and the thickness of the metal part (unoxidized) is about 0.5 μm or more and 10.9 μm or less.
[0065] In Examples 7 to 9, the oxide thickness is about 2.6 μm to 7.1 μm, and the metal part (unoxidized) thickness is about 0.8 μm to 9.8 μm. In Examples 10 to 12, the oxide thickness is about 2.5 μm to 7.1 μm, and the metal part (unoxidized) thickness is about 0.9 μm to 10.0 μm.
[0066] In Comparative Examples 1 to 4, no oxidation treatment is performed, so no oxide is formed and only the metal portion remains.
[0067] In Comparative Examples 5 to 8, the powders (Ni, Cu, Fe, Zn) added to the positive electrode active material are entirely oxidized in the oxidation treatment, and no metal portion (unoxidized portion) is formed.
[0068] 3, in Examples 1 to 12, the time until a short circuit occurs when fully charged and stored at 80° C. is 100 hours or more, which is sufficiently longer than the time until a short circuit occurs in Comparative Examples 1 to 4. In addition, as shown in Examples 1 to 12, the thicker the oxide is, the longer the time until a short circuit occurs, and in Examples 2, 3, 6, 11, 12, etc., the time until a short circuit occurs is 300 hours or more.
[0069] In Examples 1 to 12, the dissolution current value (A) at 4.5 V in CV was 7.0×10 -3 A or less, which is sufficiently smaller than the elution current values of Comparative Examples 1 to 4. In Examples 1 to 12, it was shown that the elution of metal ions is suppressed because oxides are formed on the surface layers of metal powders such as Ni, Cu, Fe, and Zn by the oxidation treatment. This suppresses the occurrence of internal short circuits in the battery (coin cell).
[0070] The cycle retention rates of Examples 1 to 12 are all 85% or more, which are sufficiently higher than the cycle retention rates of Comparative Examples 1 to 8.
[0071] 4 and 5, the LSV measurement results for the comparative example show a rise in reaction current at approximately 3.7 V, 4.0 V, and 4.3 V. In contrast, the LSV measurement results for the example show that the reaction current is suppressed in the range up to about 4.3 V.
[0072] As shown in Figures 6(b) and 6(c), oxides are detected throughout the particle. Metal parts are detected in the center of the particle, but not on the surface of the particle. The area where metal parts are detected is smaller than the area where oxides are detected. In other words, no metal parts are detected on the surface of the particle, and there are areas where only oxides are present, indicating that the metal parts (e.g., Ni) are present inside the particle, surrounded by oxides.
[0073] From the above results, it was shown that in the secondary battery (coin cell) according to the embodiment, since the positive electrode active material is provided with a plurality of particles including an oxide and a metal portion, the occurrence of an internal short circuit can be suppressed compared to the comparative example. Also, it was shown that the battery (coin cell) according to the embodiment can obtain a better cycle retention rate than the comparative example.
[0074] The oxide of the multiple particles is formed by adding metal powder such as Ni, Cu, Fe, Zn, etc. to the positive electrode active material and performing an oxidation treatment at a maximum temperature of about 300 ° C. or more and 700 ° C. or less. In other words, even if the positive electrode active material contains a trace amount of metal powder as an impurity, an oxide is also formed on the surface of the impurity by the oxidation treatment. As a result, in this embodiment, even if the metal powder is present as an impurity, it is possible to suppress the occurrence of internal short circuits and the decrease in cycle maintenance rate.
[0075] The above-described embodiment is for the purpose of facilitating understanding of the present invention, and is not intended to limit the present invention. The present invention may be modified or improved without departing from the spirit of the present invention, and equivalents thereof are also included in the present invention.
[0076] The present disclosure may also have the following configurations.
[0077] (1) A battery comprising a positive electrode, a negative electrode, and a non-aqueous electrolyte solution; The positive electrode includes a positive electrode active material and a plurality of particles including an oxide and a metal portion, The oxide contained in each of the plurality of particles includes at least one of copper oxide, iron oxide, nickel oxide, and zinc oxide. Secondary battery. (2) The oxide is present from one surface to the other surface of the positive electrode in the thickness direction of the positive electrode. The secondary battery according to (1). (3) the oxide is present in the surface layer of the particle, The thickness of the oxide is 2 μm or more and 8 μm or less. A secondary battery according to (1) or (2). (4) The metal portion is surrounded by the oxide and exists inside the particle. A secondary battery according to any one of (1) to (3). [Explanation of symbols]
[0078] 1 Secondary battery 21 Positive electrode 21A positive electrode current collector 21B Positive electrode active material layer 22 Negative electrode 22A negative electrode current collector 22B Negative electrode active material layer 23 Separator 30 particles 31 Metal Part 32 Oxides 100 Electrode laminate S1 1st page S2 side 2
Claims
1. A positive electrode, a negative electrode, and a non-aqueous electrolyte solution, The positive electrode includes a positive electrode active material and a plurality of particles including an oxide and a metal portion, The oxide contained in each of the plurality of particles includes at least one of copper oxide, iron oxide, nickel oxide, and zinc oxide. Secondary battery.
2. The oxide is present from one surface to the other surface of the positive electrode in the thickness direction of the positive electrode. The secondary battery according to claim 1 .
3. the oxide is present in a surface layer of the particle, The thickness of the oxide is 2 μm or more and 8 μm or less. The secondary battery according to claim 1 .
4. The metal portion is surrounded by the oxide and exists inside the particle. The secondary battery according to claim 1 .
Citation Information
Patent Citations
Lithium ion secondary battery
JP2009135084A
Positive electrode composition for nonaqueous electrolyte secondary battery and method for producing positive electrode slurry for nonaqueous electrolyte secondary battery
JP2013131437A
Positive electrode material for nonaqueous electrolyte secondary battery and method of producing the same, and nonaqueous electrolyte secondary battery using the positive electrode material
JP2016225277A